The Spectator,2016-11-17 - Spectator, Valdosta State University (Valdosta State University, 2016)
The Spectator, November 17, 2016. Vol. 91, no. 14. (Valdosta State University, Georgia). http://hdl.handle.net/10428/2602.
The Spectator: The Unfiltered, Uncensored Voice of the Students
Electronic Record - Downloaded online. 1 File. Converted to PDF/A (fmt/477).
Keywords: Valdosta State University; Valdosta State University -- Periodicals; Student newspapers and periodicals